Dithiocarbamate-immobilized silica coated magnetic Fe3O4 nanoparticles for solid-phase extraction of lead in shellfish - How, Fiona Ni Foong; Mohd Nasir, Mohd Hamzah; Miskam, Mazidatulakmam Akmam; Supardi, Nurul Amilin (2018)
This study describes the synthesis, characterization and application of dithiocarbamate-immobilized silica coated magnetic nanoparticles (Fe3O4-CPTS-DTC) as an adsorbent for separation and preconcentration of trace lead in shellfish. The adsorbent was characterized using FTIR, SEM and XRD. The extraction efficiency of Fe3O4-CPTSDTC was analysed using Flame Atomic Absorption Spectrometry. Parameters such as pH, adsorption-desorption time, effect of eluent and sample volume have been investigated in order to establish the optimum conditions for the determination of lead. The MSPE method was also validated using certified reference materials with good recovery.